Città e territori da vivere oggi e domani Il contributo scientifico delle tesi di laurea - NATALI, CARLO; POLI, Daniela (Territori, 2007)
Town planning entails the complex task of studying the habitat in its variegated aspects, with the objective of introducing functional transformations in response to the demands of the community. Since it is an experimental discipline, however, methods of approach and elaboration can be very different. This book represents the synthesis of the degree theses produced in the Department of Town and Territorial Planning of the University of Florence between 2000 and 2004, selected with a view to achieving a significant overview of the various issues and disciplinary areas. The volume thus addresses topical questions such as the protection of the historic identity, the rethinking of the modern city, obsolete areas and urban gaps, relational processes and spaces, sustainable development and planning, and the settlements of developing countries.